Low-Intensity Pulsed Ultrasound Protects Retinal Ganglion Cell From Optic Nerve Injury Induced Apoptosis via Yes Associated Protein - Zhou, Jia-Xing; Liu, Yun-Jia; Chen, Xi; Zhang, Xi; Xu, Jie; Yang, Ke; Wang, Dong; Lin, Sen; Ye, Jian (Frontiers in Cellular Neuroscience, 2018)
Background: Low-intensity pulsed ultrasound (LIPUS) has been used in clinical studies. But little is known about its effects on the central nervous system (CNS), or its mechanism of action. Retinal ganglion cells (RGCs) are CNS neuronal cells that can be utilized as a classic model system to evaluate outcomes of LIPUS protection from external trauma induced retinal injury. In this study, we aim to: 1) determine the pulse energy and the capability of LIPUS in RGC viability. 2) ascertain the protective role of LIPUS in optic nerve crush induced retinal injury. 3) explore the cellular mechanisms of RGC apoptosis prevention by LIPUS. Methods: An optic nerve crush model was set up to induce RGC death. LIPUS was used to treat mice eyes daily, and the retina samples were dissected for immunostaining and Western blot. The expression of yes-associated protein (YAP) and apoptosis-related proteins were detected by immunostaining and Western blot in vitro and in vivo. Apoptosis of RGCs was evaluated by TUNEL staining, the survival of RGCs and retained axons were labeled by Fluro-gold and Tuj1 antibody, respectively. Rotenone was used to set up an in vitro cellular degeneravtive model and siYAP was used to interfering the expression of YAP to detect the LIPUS protective function. Results: LIPUS protected RGC from loss and apoptosis in vivo and in vitro. The ratio of cleaved/pro-caspase3 also decreased significantly under LIPUS treatment. As a cellular mechanical sensor, YAP expression increased and YAP translocated to nucleus in LIPUS stimulation group, however, phospho-YAP was found to be decreased. When YAP was inhibited, the LIPUS could not protect RGC from caspase3 dependent apoptosis. Conclusion: LIPUS prevented RGCs from apoptosis in an optic nerve crush model and in vitro cellular degenerative model, which indicates a potential treatment for further traumatic optic nerve injury. The mechanism of protection is dependent on YAP activation and correlated with caspase-3 signaling.